1999
DOI: 10.1063/1.124676
|View full text |Cite
|
Sign up to set email alerts
|

High-quantum-efficiency 0.5 eV GaInAsSb/GaSb thermophotovoltaic devices

Abstract: We report high-performance lattice-matched GaInAsSb/GaSb thermophotovoltaic (TPV) devices with a 0.5 eV band gap. The TPV structures were grown on GaSb substrates by organometallic vapor phase epitaxy at a lower temperature (525 °C compared to 550 °C) to improve the quality of the metastable GaInAsSb alloy. The 0.5 eV TPV devices exhibit external quantum efficiency as high as 60%, which corresponds to an internal quantum efficiency of 90%, assuming 35% reflection losses. This efficiency is comparable to the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
82
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 10 publications
0
82
0
2
Order By: Relevance
“…Energy-dispersive x-ray analysis in a scanning transmission electron microscope confirmed that lighter regions are InSb-rich, while darker regions are GaAs-rich [77]. Reciprocal space mapping in HRXRD studies indicated that the broadening is also due to epilayer tilt [76].…”
Section: Effect Of Growth Kinetics On Phase Separation In Gainassbmentioning
confidence: 99%
See 2 more Smart Citations
“…Energy-dispersive x-ray analysis in a scanning transmission electron microscope confirmed that lighter regions are InSb-rich, while darker regions are GaAs-rich [77]. Reciprocal space mapping in HRXRD studies indicated that the broadening is also due to epilayer tilt [76].…”
Section: Effect Of Growth Kinetics On Phase Separation In Gainassbmentioning
confidence: 99%
“…Systematic experiments have shown that phase separation in GaInAsSb epilayers can be greatly reduced by affecting growth kinetics so that adatom surface diffusion is limited. It was found that growth temperature, growth rate, and substrate miscut had a large impact on structural and optical qualities [34,[74][75][76][77]. This huge sensitivity of material quality to growth conditions is demonstrated by comparing characterization data of two GaInAsSb layers that were grown at a GaInAsSb is further into the miscibility gap than 0.55-eV GaInAsSb.…”
Section: Effect Of Growth Kinetics On Phase Separation In Gainassbmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different alloy compositions were grown: Ga 0.89 In 0.11 As 0.09 Sb 0.91 and Ga 0.8 In 0.2 As 0.17 Sb 0.83 , which have 300 K photoluminescence (PL) peak energy at 0.6 eV and 0.5-eV, respectively. The GaInAsSb alloy composition was determined from the peak energy in 300 K PL spectra and lattice mismatch, as previously described [24]. The microstructure of GaInAsSb was studied by examining <110> cross-sections in TEM operated at 200 kV.…”
mentioning
confidence: 99%
“…GaInAsSb epitaxial layers were grown nominally lattice matched to (001) GaSb substrates with miscut angles of 2 or 6° toward (1-11)B or (101) by OMVPE as previously described [24][25]. The growth temperature was either 525 or 575 °C.…”
mentioning
confidence: 99%